Study of Erosion-Corrosion of Stainless Steel, Brass and Aluminum by Open Circuit Potential Measurements - Kabir, Kazi Bayzid; Mahmud, Iqbal (Journal of Chemical Engineering, 2011)
The PDF for this article was replaced on 16/05/2011 with minor editorial changes. - Editor Influence of flow on corrosion behavior of stainless steel, brass and aluminum was studied using electrochemical measurement techniques. Flow effect was identified by comparing erosion-corrosion with pure corrosion studies. For this purpose, open circuit potential (OCP) measurements were performed in both quiescent and flow conditions. OCP transient for the metals/alloys (stainless steel, brass and aluminum) indicated the nature and extent of corrosion on the sample by the environment (seawater and sodium carbonate). Three distinct type of curves were found for all metal-environment combinations. Increasing OCP indicated noble metal behavior while decrease in OCP indicated corrosion of material in the exposed environment. Directional shift in the OCP indicated changes in the surface phenomena. Hence, shape of these curves provides information about the extent of metal environment interaction. Experimental observations showed the applicability of open circuit measurements for on-line corrosion monitoring. Keywords open circuit potential; erosion-corrosion; electrochemical measurements; stainless steel; brass; aluminum. DOI: 10.3329/jce.v25i0.7234 Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.13-17